Temperature dependences and isotherms of galoanomagnetic properties of Bi doped PbTe crystals and thin films - Rogacheva, E. I.; Lyubchenko, S. G.; Vodorez, O. S. (Науково-технологічний комплекс "Інститут монокристалів", 2006)
The temperature dependences of galvanomagnetic properties (the Hall coefficient, electrical conductivity, charge carrier mobility) of (PbTe)₁₀₀₋ₓBiₓ (x = 0-1) alloys obtained by doping PbTe with elementary Bi and thin films prepared from these alloys were studied in the temperature range 80-300 K. On the basis of the temperature dependences, the isotherms of the properties on the Bi concentration, which had been observed earlier at room temperature, is preserved at lower temperatures. This confirms our earlier suggestion about the self-organization processes taking place in the defect subsystem of the crystal at certain Bi concentrations.

Досліджено температурні залежності (80-300 К) гальваномагнітних властивостей (коефіцієнта Холла, електропровідності, рухливості носіїв заряду) сплавів (PbTe)₁₀₀₋ₓBiₓ (x = 0-1), які одержані шляхом легування PbTe елементарним Bi, та плівок, що виготовлені з цих сплавів. На основі температурних залежностей побудовано ізотерми властивостей. Встановлено, що немонотонний характер залежностей властивостей від вмісту Bi, що спостерігався раніше при кімнатній температурі, зберігається при зниженні температури. Це підтверджує припущення, що висловлювалося раніше, про процеси самоорганізації, що йдуть у дефектній підсистемі кристала при певних концентраціях Bi.
Температурні залежності та ізотерми гальваномагнітних властивостей кристалів та тонких плівок PbTe, легованого Bi
Keywords: Hall coefficient; electrical conductivity; charge carrier mobility; defect subsystem; коефіцієнт Холла; електропровідність; рухливість носіїв заряду; дефектна підсистема